1986
DOI: 10.1002/hep.1840060616
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the effects of prednisone withdrawal on serum hepatitis B virus DNA and HBeAg in chronic active hepatitis B

Abstract: We investigated the efficacy of a short course of prednisone therapy in 20 patients with histologic evidence of chronic active hepatitis B. Sixteen of 20 prednisone-treated patients who were initially serum hepatitis B virus DNA-positive had a transient elevation of their serum ALT activity on withdrawal of prednisone. Subsequently, 14 of these 16 patients (87.5%) became persistently negative for serum hepatitis B virus DNA, and 10 also lost their HBeAg. In addition, there was a significant fall in serum ALT l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 33 publications
4
21
1
Order By: Relevance
“…The results of our trial, in which 71 % of the patients became DNA-polymerase-negative and 64% lost HBeAg from serum in the follow-up period are similar to the experi ence of Nair et al [3,12]. The reasons for the high rate of clearance of viral replication in our patients may be diverse.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The results of our trial, in which 71 % of the patients became DNA-polymerase-negative and 64% lost HBeAg from serum in the follow-up period are similar to the experi ence of Nair et al [3,12]. The reasons for the high rate of clearance of viral replication in our patients may be diverse.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, a large proportion of our cases had a very active form of disease on liver histology (bridging necrosis, active cir rhosis), and it was suggested that in such patients withdrawal of corticosteroids is likely to cause an intense T cell response against infected hepatocytes, since these pa tients are already immunologically 'primed' [ 17], Thus, patients with mild forms of CAH are supposed to be less likely to respond to therapy. However, in contrast to the study of Nair et al [3], we did not find difference in rates of viral clearance between patients with CAH type 1 and those with more advanced liver disease (CAH type II or CAH type III), but it should be noted that the groups were relatively small.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In the same way, a pronounced rebound of immune response to HBV replication with rapid tapering or abrupt discontinuance of immunosupressants such as steroids may precipitate hepatic decompensation in HBsAg-positive patients with chronic liver diseases like our patient (Case No. 5) (Schullard et al 1981;Nair et al 1986). …”
Section: Discussionmentioning
confidence: 99%